Characterisation of the wind properties in the Grande Ravine viaduct. Issue 173 (February 2018) - Bastos, Fernando; Caetano, Elsa; Cunha, Álvaro; Cespedes, Xavier; Flamand, Olivier
Abstract: This paper aims to characterise the properties of the atmospheric wind acting on a girder bridge crossing an abrupt volcanic breach at the Reunion Island, a zone frequently affected by cyclones. For that purpose, an aerodynamic monitoring system, comprising various anemometers, pressure and temperature sensors and accelerometers, is installed on the bridge. The analysis of the data recorded over a period of two years is conducted, and a comparison is made with information extracted from the design wind studies based both on wind tunnel tests of a physical model of the viaduct's surrounding topography and on historical data recorded at a meteorological station. The comparison is made in terms of the prevailing wind directions, corresponding incidences and turbulence characteristics, as well as the local variation of the wind characteristics along the viaduct span. This study identifies the influence of the walls of the ravine and the influence of the roughness and topography upstream from the viaduct on the acceleration of the flow inside the ravine and on the higher-than-predicted turbulence. Highlights: Local wind characterisation based on full-scale measurements. Comparison of full-scale observations with wind tunnel test results. Characterisation of complex topography. Systematisation of procedures for assessment of local wind properties based on full-scale and laboratory experiments.